A location value response surface model for mass appraising: An “iterative” location adjustment factor in Bari, Italy - d’Amato, Maurizio (International Journal of Strategic Property Management, 2010)
The work is focused on a new model of mass appraising including location variable. A location adjustment factor derived from a mathematical iteration was compared to the location adjustment factor based on geostatistical techniques. The work compares three different linear MRA models. The first one uses the location blind linear MRA. The second integrates the linear MRA with a location adjustment factor calculated using spatial interpolation. The second alternative is an application of Location Value Response Surface Models (O’Connor, 1982). It represents the first application of these models for mass appraising in Italy. The third approach introduces the Iterative Location Adjustment Factor. This is a factor which measure the influence of location derived from a mathematical iteration. Empirical results seem to prove the validity of Iterative Location Adjustment Factors in specific context with few observations. First Published Online: 09 Jun 2011